Effect of αc-relaxation on the large strain cavitation in polyethylene. (1st December 2020) - Lu, Ying; Lyu, Dong; Tang, Yujing; Qian, Li; Qin, Yanan; Xiang, Mingyue; Men, Yongfeng
Abstract: The large strain cavitation associated with the fragmentation of the highly oriented amorphous network was observed in the high density polyethylene (HDPE) samples over a wide range of stretching temperatures. The critical stress for initiating this cavitation in HDPE showed a strong stretching temperature dependency. Two key factors affecting the value of the critical stress for initiating large strain cavitation at different stretching regimes have been identified. Below 70 °C, the distinct weight crystallinities of HDPE at the state just before large strain cavitation were confirmed to be responsible for the change of critical stress for large strain cavitation. These differences led to a change in the number of load-bearing inter-fibrils/micro-fibrils tie chains in the highly oriented amorphous network, eventually altering the macroscopic critical stress. Above 70 °C, the continuous reduction of critical stress for large strain cavitation could be interpreted by the activation chain-diffusion inside the crystallites due to αc -relaxation. As the whole oriented fibril network of HDPE was in a dynamic state after the activation of αc -relaxation, the stability of this oriented network decreased. Thus, the critical stress for large strain cavitation reduced. Graphical abstract: Image 1 Highlights: HDPE intrinsically triggered large strain cavitation associated with the fragmentation of highly oriented amorphous network. The critical cavitation stress is temperature dependent due to αc -relaxation dependent properties of oriented network. A quick failure of linear HDPE was observed after the activation of αc -relaxation.